(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Shiitake mushrooms and chickpeas, valued for their nutritional benefits, functional properties, and environmental sustainability, are promising ingredients for alternative food development, yet limited research has explored their combined use in plant-based products. This study aims to transform shiitake mushrooms into valuable food products —specifically plant-based balls —by combining them with chickpea flour, thereby enhancing their value and promoting sustainability. Shiitake mushrooms and chickpea flour were combined in three ratios (15:35, 25:25, and 35:15) to formulate the mushroom balls. The research assessed the sensory characteristics of plant-based balls using a 9-point hedonic scale. The evaluation focused on chewiness, flavour intensity, umami, colour, saltiness, aftertaste, and overall acceptability. The research also includes physicochemical properties and calorie content of plant-based balls for nutritional labelling. Additionally, it examines the effect of cooking time (7, 10, and 13 min) on the texture and colour of the most selected plant-based ball. Sensory analysis revealed that the 35:15 ratio received the highest preference levels for overall acceptability. Consequently, it was chosen for further chemical and physical analyses. The chemical composition of the preferred plant-based ball showed moisture, protein, fat, ash, and carbohydrate levels of 53.36%, 13.48%, 1.29%, 5.25%, and 26.62%, respectively. The calorie value was 172 kcal per 100g. Hardness and chewiness decreased with longer cooking time, with 10 min being optimal. Lightness (L*) decreased from 37.44 to 13.06 as cooking time increased, with 10 min indicating medium lightness. Combining shiitake mushrooms with chickpea flour (35:15) creates a promising formulation with moderate protein content and favorable consumer preference.